Innovation as a driving force for the creation of sustainable value derived from CSR: An integrated perspective - Esther Poveda-Pareja; Bartolomé Marco Lajara; Mercedes Úbeda García; Encarnación Manresa-Marhuenda (European Research on Management and Business Economics (ERMBE), 2024)
Coastal tourism is deep into a dichotomy between its potential to provide a wide range of social and natural benefits, and its traditional link to mass models, provoking a profound debate around the generation of negative externalities. This study examines the role of innovation and strategic corporate social responsibility orientation in the relationship between CSR and corporate performance to determine the mechanisms that underlie this main relationship. To this end, a sample of 202 hotels on the Spanish coast is analysed by applying the Partial Least Square Methodology. Useful results are derived from the empirical testing of the theoretical model, such as the existence of a positive direct effect between CSR and hotel performance. Likewise, we shed light on the mediating role of innovation and the moderating effect of a strategic CSR orientation in the main relationship, providing valid solutions for both academics and managers of coastal hotels, in terms of adopting CSR practices and promoting its integration into the core business of the hotel, and further developing innovations that will boost the benefits derived from their responsible practices, as well as their strengths to overcome the barriers traditionally faced when carrying out CSR strategies.
Keywords: M14; O31; L83; 650; Innovation; Performance; Social Responsibility; Tourism